Gambaran Pengetahuan, Sikap, dan Perilaku Perawatan Diri pada Remaja Selama Menstruasi - Komsiyah; Dian Kumalasari (Universitas Ngudi Waluyo, 2026)
Puberty accompanies the growth and development of children into adolescents,marked by the onset of menarche (the first menstruation) in young girls.Maintaining reproductive health, such as practicing genital self-care duringmenstruation, is essential for adolescent girls. Good knowledge and attitudes arerequired for them to perform proper menstrual self-care. This study aims todescribe the knowledge, attitudes, and self-care behaviors during menstruationamong adolescents. The research type is descriptive quantitative with a crosssectional design. The sampling technique used was accidental sampling, with atotal of 55 respondents. The results showed that 70.9% of respondents had a goodlevel of knowledge. Regarding attitudes toward self-care, 100% were categorizedas good, while 80% of respondents' behaviors were categorized as poor. Inconclusion, while the knowledge and attitudes regarding menstrual self-careamong adolescents were found to be good, the actual behavior was poor. Furthereducation through practical demonstrations on maintaining personal hygieneduring menstruation is needed, along with a support system from various partiesto enhance the motivation of adolescent girls in maintaining menstrual hygiene.